Process development for ethanol production from cellulose-rich bagasse residues after furfural production - Bunga, Godrick Emmanuel (Stellenbosch : Stellenbosch University, 2025)
Bunga, G. E. 2025. Process Development for Ethanol Production from Cellulose-Rich Bagasse Residues after Furfural Production. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/6fbfddf3-9bf1-4612-bec0-20b4e4edb985